Prevalence of Extended Spectrum ß-Lactamase Producing Klebsiella Pneumoniae Isolates in A Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Extended-spectrum β lactamases (ESBLs) continue to be a major challenge in clinical setups world over, conferring resistance to the expanded-spectrum cephalosporins.Objectives: The aim of this study was to determine the prevalence of extended spectrum β-lactamase (ESBL) in strains of Klebsiella pneumoniae isolated from different clinical specimens in Dhaka Medical College Hospital, Dhaka, Bangladesh.Methodology: This cross sectional study was carried out at the Department of Microbiology of Dhaka Medical College, Dhaka, Bangladesh from July 2016 to June 2017. Klebsiella pneumoniae were isolated from different clinical specimens from adult hospitalized patients. These isolates were screened for ESBL production according to Clinical and Laboratory Standards Institute (CLSI) guidelines. ESBL production was confirmed by the phenotypic confirmatory double disc synergy test (DDST).Results: Among the 500 collected samples 75 Klebsiella pneumoniae were isolated. Among them, 68 isolates were selected for confirmatory tests of ESBL according to CLSI guidelines. Finally, 19 isolates were confirmed as ESBL producers by DDST (25.33%).Conclusion: In the present study, a large number of isolates are found to be ESBL producers.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 101-104